Measures to Eliminate Social Exclusion among Iraqi Displaced Population: Field Study on a Sample of in-camp Residents in Baghdad - AL Rahoomi, Salama Mohammad juma; Al-Taii, Alaa Marouf (Al-Adab Journal, 2020)
Wars everywhere have a set of consequences, the least of which is depriving individuals of their most basic rights. The right to a decent life on a homeland in which they grew up is one of the most important rights they lose. Consequently, they become displaced and homeless. They also become deprived of their basic needs such as food, drinking water, and clothing. In addition, they find themselves deprived of education and health care. This led to deprivation of political and social participation, civil rights, which in turn lead to inequality in wealth and power. The study aimed to identify the most important areas of social exclusion in the areas inhabited by the displaced, and their perceptions of exclusion and ways to prevent its consequences. The study adopted the concept of social exclusion, relying on the methodology of social survey by applying a questionnaire tool to a sample of (200) individuals in the camps of Baghdad and Anbar. The study revealed a number of facts, the most important of which is that the displaced in Baghdad are excluded in several areas, mainly the economic field. The study also concluded that the displaced have a wide and clear picture of the measures that must be taken to eliminate all forms of social exclusion.